Improving knowledge and attitude towards child marriage prevention among senior high school students - Niken Meilani; Nanik Setiyawati; Siti Rofi'ah; Tuti Sukini (Journal of Education and Learning (EduLearn), 2023)
The rate of child marriage worldwide reaches 21%. Indonesia was the 37th country with the second-highest percentage of child marriages in ASEAN. Adolescent knowledge and attitudes affect behavior in child marriages. Therefore, educational media is needed to increase knowledge and form positive attitudes in adolescents related to the maturation of age marriage. This study was to determine the effect of video on the knowledge and attitudes of adolescents about the maturation of age marriage. This research used a quasi-experimental nonequivalent control group design carried out in April-October 2022. The experimental group was given treatment through an educational video and the control group using a pocketbook. High school student was the population. Sampling technique was employed, involving 120 respondents for both groups. The research instrument used was a questionnaire which has been tested. Data analysis using statistical test software. In the video group, the mean difference test results for the level of knowledge were p=0.000 and attitude was p=0.006. In the pocketbook group, the level of knowledge was p=0.003 and attitude was p=0.314. Educational video is an effective method to improve adolescents’ knowledge and attitude about the maturation of age marriage. It can be used to prevent child marriage among adolescents.